Agricultural policies in Sub-Saharan Africa: understanding CAADP and APRM policy processes - Roukayatou Zimmermann; Michael Brüntrup; Shashidhara Kolavalli; Kathleen Flaherty (Deutsches Institut für Entwicklungspolitik (DIE), 2009)
It is widely acknowledged that a well-performing agricultural sector is fundamental for Africa's overall economic growth, as well for as addressing hunger, poverty, and inequality. However, for the last decades the sector has stagnated, it has been taxed and/or neglected by both governments and donors and has not been able to accomplish its role for development. The New Partnership for Africa's Development (NEPAD) – the economic programme of the African Union (AU) – early on recognised the importance of agriculture and the weaknesses of member countries' agricultural policies. NEPAD developed a special initiative, namely the Comprehensive Africa Agriculture Development Programme (CAADP), to improve agricultural policies on the continent. Another NEPAD initiative, the African Peer Review Mechanism(APRM), is likewise supposed to have major impacts on agriculture. This study examines how the CAADP and APRM can and do influence agricultural policies and strategies at the country level. It is based on detailed case studies conducted in Ghana and Kenya and a rapid assessment in Uganda. The key issues analysed, which, in keeping with the new aid effectiveness agenda and NEPAD principles, were supposed to improve agricultural policy processes and their impacts, are ownership, participation, use of scientific evidence, including peer review elements, and alignment. The study works out strengths and weaknesses of past agricultural policies as well as NEPAD initiatives, elaborating recommendations on how best to improve these initiatives to make them fully operational for agricultural development in Africa.
Keywords: 330